PENGARUH PERASAN LABU SIAM TERHADAP PERUBAHAN TEKANAN SISTOLIK DAN DIASTOLIK DI DUKUH WONOREJO DESA TEMUWANGI KECAMATAN PEDAN - Ernawati .; Mukhamad Nur Khamid; Yeni Rusyani (STIKES DUTAGAMA KLATEN, 2015)
Background: Primary hypertension is 90% of the hypertension sufferers cases. In the longterm, if it is not cured immediately, it will lead artery’s damage in the body up to the organ which gets the blood supply from the artery and complication of the other organs will occur. Chayote is a vegetable commonly consumed by people to lower the blood pressure. Objective: To identify the influence of chayote’s extract towards the change of the systolic and diastolic pressures of hypertension’s sufferers in Wonorejo, Temuwangi village, Pedan sub district. Method: Experimental design with time series method. This research was done in nine days which consisted of three days for observation before the treatment, three days for the treatment, and three days after the treatment. The extract of chayote as much as 200ml as given twice per day in the morning and in the afternoon and afterwards the measurement of the systolic and diastolic pressure during the nine days as done once every morning. There were twenty five respondents with total sampling method. The date was processed using parametric statistic tests with t-test technique: paired two samples for means. Results: There was the change of systolic and diastolic pressure. Before the treatment, the average of systolic pressure had been 158.32 mmHg. During the treatment, the average of systolic pressure was 146.20 mmHg. After the treatment, the average systolic pressure was 132.32. Mean while, the average of diastolic pressure before the treatment had been 82.28 mmHg. During the treatment, the average of systolic pressure was 79.20 mmHg. After the treatment, the average of systolic pressure was 70.80 mmHg. Conclusion: The extractof chayote affected the change of systolic and diastolic pressures of primary hypertension’s sufferers in Wonorejo, Temuwangi village, Pedan sub-district.